Controls on the Fate of Dissolved Organic Carbon Under Contrasting Upwelling Conditions - Bif, Mariana B.; Hansell, Dennis A.; Popendorf, Kimberly J. (Frontiers in Marine Science, 2018)
To understand controls on the production and remineralization of recalcitrant dissolved organic carbon produced in association with positive net community production, we simulated upwelling systems of different intensities by combining and incubating whole seawater collected from different depths in the Florida Strait (27˚N, ~79˚W). The natural microbial communities in the treatments grew under controlled light and temperature for 15 days (i.e., the autotrophic phase); they were subsequently incubated for 35 days in the dark heterotrophic phase. We analyzed the phytoplankton composition and pigment fluorescence intensity during the light phase, and dissolved organic and inorganic variables during both phases. Initial high or low availability of inorganic nutrients controlled phytoplankton growth and the magnitude of NCP. In the strong upwelling treatment, with higher initial inorganic nutrients, 25% of NCP accumulated as DOC after 15 days; however, this material was in turn fully remineralized during the dark phase. In contrast, low nutrients in the weak upwelling treatment not only limited NCP, but also the fraction of NCP accumulated as DOC (11%). Surprisingly, most of this fraction resisted microbial remineralization in the dark phase, suggesting that upwellings of different intensities affect the quality of dissolved organic matter produced, thereby affecting the timing and location of its remineralization and, hence, its prospects for export to the deep ocean.